Formulasi Self Nano-Emulsifying Drug Delivery System (SNEDDS) Ibuprofen dengan VCO dan Kombinasi Surfaktan - Muhamad Handoyo Sahumena; Suryani Suryani (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Ibuprofen is one of the Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) class of propionic acid derivatives which has potent anti-inflammatory and antipyretic activity. The solubility of ibuprofen is disadvantageous because it is practically insoluble and has poor dissolution. The aim of this study was to overcome the solubility of ibuprofen through a stable SNEDDS formula. One way to overcome the solubility of ibuprofen is to prepare nanoemulsions using the Self-Emulsifying Drug Delivery System (SNEDDS) technique. SNEDDS is a form of preemulsion drug which spontaneously forms nanoemulsion when it encounters the aqueous phase in the digestive tract. Parameters for the success of the SNEDDS formula include emulsification time, stability, and droplet size using a particle size analyzer (PSA). The SNEDDS formulation was carried out by mixing span 80 and tween 20, PEG 400 and VCO as the oil phase. The characteristics of SNEDDS ibuprofen include homogeneity of SNEDDS, clarity, transmittance, emulsification time, and droplet size. The composition of the optimum formula for SNEDDS ibuprofen is 1 mL of VCO; 1 mL PEG; 7 mL tween 20; 1 mL span 80. The formula shows good homogeneity, is clear with emulsification time of 15 seconds, transmittance is 92.69%, and droplet size is 221.9 nm.